Remarkable damage along with poor quality of life in Takayasu arteritis: cross-sectional results of a long-term followed-up multicentre cohort - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2017)
Objective. We aimed to assess the outcome of a large Takayasu arteritis (TAK) cohort using the vasculitis damage index (VDI) and quality of life (QoL) scale, tools which have been validated for vasculitis. Methods. Disease activity, damage and QoL were cross-sectionally evaluated in 165 TAK patients from 6 centres. SF-36 were applied to 51 age-matched healthy controls (HC). Persistent activity for months was considered as treatment resistance (r-TAK). The correlation between VDI, clinical characteristics and mental (MCS)/physical (PCS) component scores of SF-36 were analysed. SF-36 and VDI scores were compared between TAK subgroups and HC. Results. The median age, follow-up time and disease duration were 40 (17-68), 60 (6-384), and 72 (6-396) months, respectively. 35% of them were r-TAK. VDI scores (VDIs) in TAK 4 (1-12) were mainly due to the disease itself [4 (1-10)]. VDIs in r-TAK were significantly higher than nr-TAK [5 (212) vs. 3 (2-10), p<0.001)1. In the TAK patients, MCS and PCS were found as 43 10 and 38 11, respectively. A high proportion of poor MCS (70%) and PCS (80%) were demonstrated in TAK. A significantly negative but weak correlation was observed between VDI and MCS (p=0.003, r=-0.23), PCS (p<0.001, r=-0.34). Higher VDIs were detected in patients with PCS <50 [5 (.1-12) vs. 2 (1-6) p<0.001)]. SF-36 score was significantly lower in TAK than KC. Conclusion. Disease-related damage mainly caused by peripheral vascular involvement was more predominant than treatment-related damage without reaching the level of severe damage scores, but contributing to poor QoL, in the TAK cohort.
Keywords: vasculitis; Takayasu arteritis; vasculitis damage index; quality of life; ANTIBODY-ASSOCIATED VASCULITIS; HEALTH SURVEY SF-36; WEGENERS-GRANULOMATOSIS; SYSTEMIC VASCULITIS; MENTAL-HEALTH; DISABILITY; SURVIVAL; AORTITIS; VALIDITY; DISEASE